Strategi Program Pemberdayaan Masyarakat Di Desa Puncu Kabupaten Kediri Jawa Timur - Aynut Dhobit; Abbas Sofwan Matlail Fajar (UIN Syarif Hidayatullah Jakarta, 2022)
Empowerment programs with intensive assistance are an alternative to accelerating community economic growth. This study aims to analyze how community pasticipation in the “Desa Gemilang” Empowerment program is run by LAZ Al Azhar, and the problems and obstacles that arise in its implementation in the field. Trough qualitative research methods using a descrptive approach. This data collection. Technique is done by interview, observation and document study. The research was conductes in Puncu Village, Puncu District, Kediri Regency, East Java Province. The Results of this study indicate that community participation in this program is quite good. The program focuses on four sectors, namely : Economy, Education, Religion, and Health. The community is very enthusiastic and participatory with various kinds of activities that are carried out and of course have a significant impact on change. However, there are some people who tend to be volatile because they have not been touched by the benefid of the programs being implemented.